Globalization Issues in Education Policy Toward World Class Education (WCE): A Case Study at UIN Syarif Hidayatullah Ciputat Timur - Septariani, Septariani; Kaspul Anwar Us; Fridiyanto (Future Tecno-Science Publisher, 2025)
The pressures of globalization have pushed higher education institutions to reorient their policies beyond local needs toward international competitiveness by aligning with World Class Education (WCE) standards. This study explores how UIN Syarif Hidayatullah Ciputat responds to such global demands through its education management policies. Using a qualitative single case study design adapted from Yin, data were collected via in-depth interviews with policy stakeholders, document analysis of strategic and academic policy, and participatory observation. Thematic analysis, following Braun and Clarke’s framework, was employed to interpret findings. Results show that UIN Ciputat's policy response is reflected in its Strategic Plan 2020–2024 through five priority programs emphasizing teaching quality, global publication, human resource development, infrastructure modernization, and global partnerships. Influential external policies, particularly the Ministry of Education’s Key Performance Indicators (IKU), have encouraged restructuring efforts toward international accreditation and improved global visibility. Implementation strategies are executed through strategic faculty-level agendas and institutional coordination mechanisms involving regular monitoring and evaluation. Despite several constraints—including budget reallocation due to COVID-19, low international publication output, and digital infrastructure gaps—the university has leveraged its autonomous status (PTN-BH), regional rankings, global networks, and government incentive funds to advance its internationalization agenda. This research concludes that while UIN Ciputat has made substantial progress, further optimization in funding, collaboration, and capacity-building is necessary to fully achieve WCE standards.